2022
DOI: 10.1111/apm.13260
|View full text |Cite
|
Sign up to set email alerts
|

Screening the Tocriscreen™ bioactive compound library in search for inhibitors of Candida biofilm formation

Abstract: Biofilms formed by Candida species present a significant clinical problem due to the ineffectiveness of many conventional antifungal agents, in particular the azole class. We urgently require new and clinically approved antifungal agents quickly for treatment of critically ill patients. To improve efficiency in antifungal drug development, we utilized a library of 1280 biologically active molecules within the Tocriscreen 2.0 Micro library. Candida auris NCPF 8973 and Candida albicans SC5314 were initially scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…There are many examples of such efforts in the recent literature aimed specifically at the identification of repositionable compounds with anti- Candida biofilm inhibitory activity [ 68 ]. While initial studies mostly used C. albicans , most recently these studies have been also extended to C. auris , due to the urgency in identifying new compounds effective against this multi-drug resistant emergent species [ 67 , 69 , 70 ]. A few notable leading repositionable candidates, among others, identified during this work are auranofin, ebselen, alexidine and niclosamide, with ongoing studies aimed at further evaluating their activity both in vitro and in vivo, including in biofilm-relevant models, and advancing their development as antifungals, with emphasis on the treatment of resistant Candida infections, including biofilm-associated candidiasis [ 69 , [71] , [72] , [73] , [74] ].…”
Section: The Futurementioning
confidence: 99%
“…There are many examples of such efforts in the recent literature aimed specifically at the identification of repositionable compounds with anti- Candida biofilm inhibitory activity [ 68 ]. While initial studies mostly used C. albicans , most recently these studies have been also extended to C. auris , due to the urgency in identifying new compounds effective against this multi-drug resistant emergent species [ 67 , 69 , 70 ]. A few notable leading repositionable candidates, among others, identified during this work are auranofin, ebselen, alexidine and niclosamide, with ongoing studies aimed at further evaluating their activity both in vitro and in vivo, including in biofilm-relevant models, and advancing their development as antifungals, with emphasis on the treatment of resistant Candida infections, including biofilm-associated candidiasis [ 69 , [71] , [72] , [73] , [74] ].…”
Section: The Futurementioning
confidence: 99%
“…Moreover, a screen of the FDA‐approved Prestwick chemical library identified suloctidil and Ebselen as effective compounds against C. auris (131). Most recently it was shown that Toyocamycin and Darapladib showed promising activity against C. albicans and C. auris biofilms (132). However, to date, none of the compounds proved to have antifungal activity in libraries screening reached clinical settings (133).…”
Section: Current Antifungal Approaches To Managing Candida Infectionsmentioning
confidence: 99%